Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dengan Masalah Open-Ended sebagai Upaya Meningkatkan Kreativitas Siswa - Susi Anika (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2022)
This research is based on the low creativity of students and the low active activity of students in solving mathematical problems caused by the low ability of teachers to understand learning models in learning activities. Less relevance of the learning model applied by the teacher to the objectives and characteristics of mathematics. This study aims to increase students' creativity and activity in solving mathematical problems by applying the Jigsaw type cooperative learning model. This research is a Classroom Action Research conducted at SMK Negeri 2 DEPOK with the research subject being class XI Boga III with the object of research being the application of the Jigsaw type cooperative learning model with open-ended problems as an effort to increase student creativity. The results of the data analysis in the first cycle showed that the average creativity value was 67.75 or 70% of the number of students who took the test had a minimum level of creativity in the sufficient category and 30% had a creativity level below the sufficient category. In the second cycle, the average value of the creativity test was 76.94%, at least the sufficient category and 10% had the creativity level below the sufficient category. Based on the results in cycles I and II, it can be concluded that the application of Jigsaw cooperative learning can increase students' creativity and the level of student activity during learning has met the targets applied. Keywords: Mathematics, Cooperative Learning, Jigsaw, Student Creativity